Modulation of cortical resting state functional connectivity during a visuospatial attention task in Parkinson's disease - Veréb, Dániel; Kovács, Márton Attila; Antal, Szabolcs; Kocsis, Krisztián; Szabó, Nikoletta; Kincses, Bálint; Bozsik, Bence; Faragó, Péter; Tóth, Eszter; Király, András; Klivényi, Péter; Zádori, Dénes; et al. (Frontiers in Neurology, 2022)
Visual dysfunction is a recognized early symptom of Parkinson’s disease (PD) that partly scales motor symptoms, yet its background is heterogeneous. With additional deficits in visuospatial attention, the two systems are hard to disentangle and it is not known whether impaired functional connectivity in the visual cortex is translative in nature or disrupted attentional modulation also contributes. In this study, we investigate functional connectivity modulation during a visuospatial attention task in PD patients. 15 PD and 16 age-matched healthy controls performed a visuospatial attention task while undergoing fMRI, in addition to a resting-state fMRI scan. Tensorial independent component analysis was used to investigate task-related network activity patterns. Independently, an atlas-based connectivity modulation analysis was performed using the task potency method. Spearman’s rank correlation was calculated between task-related network expression, connectivity modulation and clinical characteristics.Task-related networks including mostly visual, parietal and prefrontal cortices were expressed to a significantly lesser degree in PD patients (p < 0.027). Resting state functional connectivity did not differ between the healthy and diseased cohort. Connectivity between the precuneus and ventromedial prefrontal cortex was modulated to a higher degree in PD patients (p < 0.004), while connections between the posterior parietal cortex and primary visual cortex, as well as the superior frontal gyrus and opercular cortex were modulated to a lesser degree (p < 0.001 and p < 0.011). Task-related network expression and superior frontal gyrus – opercular cortex connectivity modulation were significantly associated with UPDRSIII motor scores and Hoehn-Yahr stages (R = -0.72, p < 0.006 and R = -0.90, p < 0.001; R = -0.68, p < 0.01 and R = -0.71, p < 0.007). In conclusion, task-related networks function differently in PD patients in association with motor symptoms, whereas impaired modulation of visual and default-mode network connectivity was not correlated with motor function.